WEATHER DAN PENGARUHNYA TERHADAP STOCK RETURN - Inka Natasya Hagaina Bukit; Sri Vandayuli Riorini (Universitas Trisakti, 2012)
Research on psychology shows that sunny weather has effect toward mood. Some researchers found that mood has significant effect toward Stock return. This paper examines relationship between Weather in Indonesia, especially in Jakarta with Stock return of LQ 45 Index. This research examine relationship between Weather and Stock return directly and indirect (using Mood as intervening variable). This research analyze that relationship during 2009 to 2010. However, because Weather in Jakarta is relatively homogen, there is no significant effect of Weather toward Stock return of LQ 45 Index.Keywords: Weather, Mood, Stock return, LQ 45 Index